Engineered nanoparticles for the treatment of Alzheimer’s disease - Jia, Jia; Zhao, Shuang; Zhao, Jinghan; Gao, Yun (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is one of the most common diseases characterized by neurodegeneration and is becoming a major public health problem worldwide. AD is manifested mainly by progressive impairments in cognition, emotion, language and memory in the elderly population. Many treatment strategies have been explored for decades; however, there is still no effective way to address the root cause of AD pathogenesis, only to target symptoms to improve patient cognitive outcomes. Intracerebral administration is difficult because of the challenges posed by the blood‒brain barrier (BBB). NPs are materials with sizes between 1 and 100 nm that can improve biocompatibility, extend the half-life, transport macromolecules, be delivered across the BBB to the central nervous system, and exhibit good targeting capabilities. NPs can provide new ideas for the treatment of AD in terms of their antiaging, antineuroinflammatory, antioxidative, and nerve repair-promoting effects. In this manuscript, we first describe the relationship between AD and the BBB. Second, we introduce the application of nanoparticles for AD treatment. Finally, we summarize the challenges faced by nanoparticles in the treatment of AD.